Geological characteristics and controlling factors of deep tight gas sandstone reservoirs in the Upper Paleozoic of the western Ordos Basin, northwest China - Zou, Chengyu; Fu, Siyi; Hu, Jianling; Hou, Linjun; Chen, Anqing; Xia, Yuqing; Liu, Hao; Yu, Yu; Chen, Hongde (Frontiers in Earth Science, 2025)
Recent exploration has confirmed industrial gas flows from several wells in the western Ordos Basin, suggesting considerable hydrocarbon exploration potential. However, prior research on characteristics of tight sandstone reservoirs, diagenetic evolution, and controlling factors in the Upper Paleozoic of western Ordos Basin remains limited. Here, underpinned by extensive cast thin-section identification and integrated with field emission scanning electron microscopy, nuclear magnetic resonance, and mercury intrusion porosimetry, we investigated the characteristics of tight sandstone reservoirs in the western part of the Upper Paleozoic strata of the Ordos Basin and examined the impact of various factors on the formation of high-quality reservoirs. There are differences in sandstone composition and type, and reservoir properties among different formations of the Upper Paleozoic of western Ordos Basin. The main pore types in the Carboniferous Yanghugou Formation and the Permian Taiyuan Formation were intergranular pores and dissolution pores of lithic fragments, whereas in the Permian Shanxi Formation and He 8, the main pore types were intercrystalline pores of clay minerals and dissolution pores of lithic fragments. In terms of physical properties, the reservoirs of the Upper Paleozoic in the western Ordos Basin have low porosity and low permeability. However, the Permian Taiyuan Formation and He 8 demonstrate better pore-throat connectivity than other stratigraphic levels. The formation of high-quality reservoirs in the Upper Paleozoic of the western Ordos Basin is governed by multiple factors. The Permian Shihezi and Shanxi formations within the alluvial plain facies, Taiyuan Formation barrier bar facies, and Yanghugou Formation delta front facies exhibited the best physical properties. Variations in the original parent rock led to different types of reservoir rock fragments, with a higher content of porosity-enhancing rock fragments correlating to stronger dissolution effects. Diagenetic processes influence reservoir preservation and development, with rapid burial and compaction being the main causes of densification in the Yanghugou Formation. Cementation impacts reservoir interactions differently over time. Fracture systems in the study area play a key role in improving reservoir permeability. This study offers a scientific foundation for energy-efficient exploration of low-permeability craton basins and new insights for predicting unconventional resources in global marine-to-continental sedimentary systems.